Studies on the effect of doping agent on the structure of polyaniline - Melad, Omar; Jarur, Mariam (Publishing House of Lviv Polytechnic National University, 2016)
Polyaniline (PANI) doped with hydrochloric acid (HCl), sulpharic acid (H2SO4) and formic acid (HCOOH) was synthesized by a chemical oxidative polymerization technique. The oxidizing agent used for this method is potassium dichromate. The polymer products were characterized by FTIR and UV-visible spectroscopy. The FTIR results showed that the doping degree of PANI-HCOOH is the greatest one. A successful doping of HCOOH in PANI was observed in UV-visible spectroscopy. Three steps decomposition observed from the thermo gravimetric analysis (TGA). Оксидаційною полімеризацією синтезований поліанілін (ПАНІ) з додатками хлорної (HCl), сульфатної (H2SO4) і мурашиної кислоти (НСООН). Біхромат калію використовується як окиснювач. Отримані продукти охарактеризовані за допомогою Фур‘є та УФ-спектроскопії. Показано, що найкращі результати отримані при додаванні НCOOH, що підтверджується УФ-спектроскопією. За допомогою термогравиметричного аналізу визначено три стадії розкладу.
Дослідження впливу допантів на структуру поліаніліну
Keywords: polyaniline; H2SO4; conductivity; thermal analysis; FTIR; dopant; поліанілін; провідність; термічний аналіз; Фур’є-спектроскопія; допант